PERAN ORANG TUA DALAM PEMBINAAN AKHLAK ANAK DI KELURAHAN MATA AIR KECAMATAN REOK KABUPATEN MANGGARAI NTT - Sulastri; Martini; Aidil Sudarmono, Muh.; Syahrul, Muhammad; Sumardin, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to understand and describe the role of parents in the moral development of children in Mata Air Subdistrict, Reok District, Manggarai Regency, East Nusa Tenggara. Children are a trust from Allah SWT and must be educated from an early age, especially in terms of moral and spiritual aspects. In this context, the family—particularly parents—plays a vital role as the first educators in instilling moral values such as honesty, responsibility, politeness, and respect for others. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results of the study indicate that parents carry out their roles through role modeling, habituation, guidance, and supervision of their children in daily life. Parents not only guide their children through verbal advice but also by providing real-life examples in behavior and attitude. Supporting factors for the role of parents include religious awareness, quality time with children, and good communication. Meanwhile, inhibiting factors include limited religious knowledge, negative environmental influences, and time constraints due to work commitments.